Економічні ризики в сфері послуг регіональної туристичної дестинації - Кукіна, Наталя Володимирівна; Трусова, Анастасія; Kukina, Natalia; Trusova, Anastasiia (Запоріжжя : ТДАТУ, 2023)
UA: У статті проведено дослідження економічних ризиків в сфері послуг регіональної туристичної дестинації. Виконано оцінку рівня ризику функціонування регіональних туристичних дестинацій України. Розроблено оптимізаційні методи управління ризиками безпечного функціонування та надання послуг суб’єктами регіональних туристичних дестинації в Україні. Оптимізовано структурні складові безпечного функціонування потенціалу розвитку ринку туристичних послуг, що надаються суб’єктами регіональних туристичних дестинацій України. EN: The economic efficiency of tourist destinations in Ukraine is being actively developed on the basis of available resources and has a sufficient level of tourist infrastructure, which, in connection with the appropriate price policy, is sufficiently competitive on the international market of tourist services. At the same time, the main priority of modern state policy in the spheres of the tourism industry of Ukraine is the minimization of external risks and a change in the direction of regulation of the safe functioning of the development potential of the tourist services market, which should be transferred to the regional and local level. The purpose of the article is to study the theoretical and methodological aspects of the formation of a safe potential for the development of the tourist services market in Ukraine and the optimization of its structural components. Identified types of risks to the safe functioning of the development potential of the tourist services market. It was determined that the highest level is characterized by currency risks in the context of international tourist activity of subjects of regional tourist destinations (4.1%). Tourists with a sufficient level of solvency did not reduce spending on recreation and tourism. Inflation (3.7%) is an influential internal risk for the country that prevents the safe development of the tourist market. Military conflicts in the state have a negative impact on tourism enterprises that specialize in foreign (inbound) tourism (the risk level is 3.5%). A fairly high level of risk is associated with strict requirements for crossing the border in border areas (3.6%). The most essential components of the safe functioning of the tourist market development potential in the regional tourist destinations of Ukraine in a competitive environment are: harmonization of state regional policy and the activities of local authorities with the aim of stimulating tourism activities of subjects and obtaining economic effect, in the field of using information technologies and realizing one's own competitive advantages.
Economic risks in the field of services of a regional tourist destination
Keywords: зовнішні економічні ризики; потенціал; розвиток; ринок туристичних послуг; туристична дестинація; external economic risks; potential; development; tourist services market